Correlational study of the core values-based pancasila student profile strengthening project (P5) and student character formation at the senior high school level - Carolus Patampang; Patrio Tandiangga; Frans Fandy Palinoan; Cornelius Arnoltus (Jurnal Konseling dan Pendidikan, 2026)
This study examines the relationship between the implementation of the Pancasila Student Profile Strengthening Project (P5) based on core values and student character formation at the senior high school level. Using a quantitative correlational approach, data were collected through questionnaires distributed to 157 students via convenience sampling. Instruments were validated through validity and reliability testing, with Cronbach’s alpha values of 0.707 (P5 instrument) and 0.831 (character instrument). Regression analysis revealed a statistically significant positive association between P5 implementation and student character formation (β = 0.591, p < .001). The coefficient of determination (R² = 0.349) indicates that P5 implementation explains 34.9% of the variance in student character—classified as a large effect size according to Cohen’s (1988) benchmarks for behavioral sciences—while the remaining 65.1% of variance is attributable to factors outside the scope of this model, such as family environment, peer influence, and prior schooling. These findings suggest that the core values-based P5 project is a meaningful contributor to student character development. However, given the cross-sectional design and single-school convenience sample, generalizations should be made with caution. Future studies employing longitudinal designs and diverse school samples are recommended to strengthen causal inferences.